Polydopamine modified and cupric peroxide loaded ZIF8 nanoparticles and application thereof

By designing ZIF8 nanoparticles with polydopamine modified and copper peroxide-loaded, the problem of limited efficacy of CDT was solved, and efficient production of -OH in tumor tissues was achieved, which significantly inhibited tumor growth and had good biocompatibility.

CN119385981APending Publication Date: 2025-02-07AFFILIATED HOSPITAL OF NANTONG UNIV

Patent Information

Application Number
CN202411581177.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing chemodynamic therapy (CDT) has limited efficacy in osteosarcoma treatment, mainly due to insufficient H2O2 concentration and the consumption of -OH generated by overexpressed reducing substances in tumor cells, thereby weakening the therapeutic effect.

Method used

A polydopamine-modified ZIF8 nanoparticles (CuO2@ZIF8@PDA NPs) were designed to release CuO2NPs in tumor tissues, and use Cu2+ to react with GSH to generate Cu+, and accelerate Fentons under the action of photothermal Reaction, produce -OH.

Benefits of technology

This system independently generates hydroxyl free radicals in the weakly acidic tumor microenvironment, effectively killing tumor cells. In vitro and in vivo experiments showed good anti-tumor efficacy and was low in normal cytotoxicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119385981A_ABST
    Figure CN119385981A_ABST
Patent Text Reader

Abstract

The invention discloses a polydopamine modified and cupric peroxide loaded ZIF8 nano particle and application thereof, and belongs to the technical field of medicine preparation. According to the invention, a zeolite imidazoline framework 8 is used as a matrix, CuO2NPs is uniformly modified in the zeolite imidazoline framework 8 to form CuO2 (at) ZIF8NPs, and the surface of the CuO2 (at) ZIF8NPs is coated with a polydopamine film in the form of a film. The invention constructs multifunctional ZIF8NPs (CuO2 (at) ZIF8 (at) PDANPs) which is coated with PDA and loaded with CuO2NPs, and the multifunctional ZIF8NPs (CuO2 (at) ZIF8 (at) PDANPs is used for CDT of thermal enhancement OS. The CuO2 (at) ZIF8 (at) PDA NPs is combined with a photothermal effect and a chemodynamic therapy, shows good biocompatibility and an anti-tumor curative effect, has a potential application prospect in the aspect of osteosarcoma, and provides a new thought and method for treatment of osteosarcoma.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of drug preparation, and in particular relates to polydopamine-modified, copper peroxide-loaded ZIF8 nanoparticles and applications thereof. Background Art

[0002] Osteosarcoma (OS) is a common malignant bone tumor in adolescents, often accompanied by the risk of distant metastasis and recurrence. Therefore, early diagnosis and treatment are the focus of current clinical treatment. Traditional treatments for osteosarcoma include surgery and postoperative chemotherapy. However, due to the strong heterogeneity of osteosarcoma tissue, poor targeting, large toxicity and side effects of chemotherapy drugs, strong drug resistance, easy metastasis and recurrence of tumors, etc., the prognosis of osteosarcoma is still poor. Therefore, the development of new treatment methods has become a research hotspot for the treatment of osteosarcoma. In recent years, radical therapies including photodynamic therapy, sonodynamic therapy and radiotherapy have become important research directions for tumor treatment due to their simplicity and high efficiency. Chemodynamic therapy (CDT) is a new type of therapy based on free radicals. It uses metal ions with Fenton or Fenton-like reaction activity to convert hydrogen peroxide (H2O2) into the most toxic reactive oxygen species (ROS) - hydroxyl radicals (-OH). Hydroxyl radicals interact with tumor cells, trigger lipid peroxidation and other reactions, induce iron allergy, and kill tumor cells. This treatment approach is minimally invasive and highly tumor-specific and has been successfully used in the treatment of osteosarcoma.

[0003] Although CDT has great potential in cancer treatment, its efficacy still faces challenges: (1) Although the level of H2O2 in tumor tissue is higher than that in normal tissue, the concentration required for CDT is still relatively low and insufficient to continuously generate -OH; (2) Reducing substances (such as glutathione GSH, etc.) overexpressed in tumor cells will consume the generated -OH, thereby weakening the therapeutic effect of CDT; (3) Single CDT treatment often fails to achieve satisfactory therapeutic effects, so multiple treatment methods are needed. Therefore, strategies such as providing exogenous H2O2, clearing GSH in tumor tissue, or CDT-based combined therapy are considered to be effective means to enhance the therapeutic effect of CDT.

[0004] Copper peroxide nanoparticles (CuO2NPs) can be decomposed into Cu 2+ and H2O2. Cu 2+ It can be used as a catalyst similar to the Fenton reaction, catalyzing the decomposition of H2O2 to generate -OH. 2+ It can also react with GSH in tumor tissues, consuming GSH and generating Cu with stronger Fenton-like catalytic activity. +Therefore, CuO2 is an ideal CDT agent. However, the small size of CuO2NPs (less than 10nm) hinders its targeted accumulation in tumor tissues through the EPR effect, making it easily cleared by the kidneys. + CuO2NPs have high biotoxicity to normal cells, so it is necessary to target and deliver CuO2NPs to tumor tissues. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a polydopamine-modified, copper peroxide-loaded ZIF8 nanoparticle and its application. The present invention constructs multifunctional ZIF8NPs (CuO2@ZIF8@PDANPs) coated with polydopamine (PDA) and loaded with CuO2NPs for CDT of thermally enhanced OS.

[0006] The purpose of the first aspect of the present invention is to provide a polydopamine-modified, copper peroxide-loaded ZIF8 nanoparticle, which uses zeolite imidazoline framework-8 as a matrix, and CuO2NPs are uniformly modified in the zeolite imidazoline framework-8 to form CuO2@ZIF8 NPs, and the polydopamine film is coated on the surface of the CuO2@ZIF8 NPs in the form of a film.

[0007] Nano drug delivery systems target drugs to tumor tissues in a passive or active manner, reducing drug toxicity and side effects. Zeolite imidazoline framework-8 (ZIF8) is a metal organic framework (MOF) nanomaterial with high porosity, strong drug loading capacity, easy surface modification, good biocompatibility, weak acid degradation and drug release for tumor tissues, and is an ideal drug carrier. Photothermal therapy (PTT) can increase the temperature of local tumor tissues, accelerate Fenton / Fenton-like reactions, and effectively improve ROS generation and CDT efficacy. Polydopamine (PDA) is a commonly used photothermal material with good biocompatibility and photothermal conversion efficiency. The present invention constructs multifunctional ZIF8NPs (CuO2@ZIF8@PDA NPs) coated with PDA and loaded with CuO2NPs for CDT of thermally enhanced OS. After injection, CuO2@ZIF8@PDA NPs accumulate in tumor tissues through enhanced permeation and retention effect (EPR). In the weakly acidic tumor environment, ZIF8 degrades and releases CuO2NPs, which decompose in the acidic environment to produce H2O2 and Cu 2+ .Cu 2+ Reacts with GSH overexpressed in tumor cells, consumes GSH and generates Cu + .Cu 2+ and Cu +Both catalyze the decomposition of H2O2, triggering a Fenton-like reaction to produce -OH. At the same time, PDA can not only generate heat under near-infrared laser irradiation, increase the temperature of tumor tissue, and promote the generation of -OH, but also react with GSH, consume GSH, and enhance the efficacy of CDT. This system integrates the generation of hydroxyl radicals enriched in tumor tissue, GSH consumption, and heat-enhanced CDT, and has shown good therapeutic effects in osteosarcoma mouse models.

[0008] The second aspect of the present invention is to provide a method for preparing polydopamine-modified, copper peroxide-loaded ZIF8 nanoparticles, using a methanol solution of Zn(NO3)2 and 2-methylimidazole as raw materials, adding CuO2NPs during the preparation of zeolite imidazoline framework-8, and obtaining CuO2NP-modified zeolite imidazoline framework-8, i.e., CuO2@ZIF8 NPs; and then in situ polymerization is performed on the surface of the CuO2@ZIF8 NPs to form a polydopamine film, and thus obtaining polydopamine-modified, copper peroxide-loaded ZIF8 nanoparticles.

[0009] Furthermore, a method for preparing polydopamine-modified, copper peroxide-loaded ZIF8 nanoparticles comprises the following steps:

[0010] Polyvinyl pyrrolidone was added to the aqueous solution of copper salt, and then alkali solution and hydrogen peroxide were added in sequence under stirring. After the reaction was complete, the CuO2NPs coated with PVP were obtained by centrifugation.

[0011] The methanol solution of Zn(NO3)2 and the methanol solution of 2-methylimidazole were respectively added dropwise to the methanol suspension of CuO2NPs for reaction, and the CuO2@ZIF8 NPs were obtained by centrifugation.

[0012] The CuO2@ZIF8 NPs are dispersed in anhydrous methanol, and a dopamine solution is added dropwise under stirring to form a polydopamine film on the surface of the CuO2@ZIF8 NPs, thereby obtaining polydopamine-modified, copper peroxide-loaded ZIF8 nanoparticles.

[0013] Preferably, the copper salt is copper chloride, copper nitrate or copper sulfate; further preferably, the copper salt is copper chloride;

[0014] Preferably, the alkali solution is sodium hydroxide or potassium hydroxide; further preferably, the alkali solution is sodium hydroxide.

[0015] Preferably, the mass ratio of the CuO2@ZIF8 NPs to dopamine is 1:(0.1-1); the dopamine solution is dopamine dissolved in a Tris buffer solution, pH=8.5, and the concentration is 1.5 mg / mL.

[0016] In a more preferred embodiment, the mass ratio of the CuO2@ZIF8 NPs to dopamine is 20:3.

[0017] Preferably, the mass ratio of CuO2NPs, Zn(NO3)2 and 2-methylimidazole is 5:73:82.

[0018] Preferably, the addition ratio of the aqueous solution of the copper salt to polyvinyl pyrrolidone is 0.05 mol: 500 mg; and / or the molar ratio of the aqueous solution of the copper salt to the hydrogen peroxide is 0.05: 1; and the flow rate when the hydrogen peroxide is added dropwise is 10 μL / min.

[0019] Preferably, the reaction time for preparing the CuO2NPs is 30min; and / or the reaction time for preparing the CuO2@ZIF8NPs is 2h; and / or the reaction time for forming a polydopamine film on the surface of CuO2@ZIF8NPs is 4h.

[0020] The third aspect of the present invention is to provide the use of polydopamine-modified, copper peroxide-loaded ZIF8 nanoparticles in the preparation of anti-osteosarcoma drugs.

[0021] Furthermore, the anti-osteosarcoma drug is a drug for treating osteosarcoma with photothermal enhanced chemodynamic therapy.

[0022] The present invention has the following technical effects:

[0023] The present invention successfully designed and prepared CuO2@ZIF8@PDA NPs for photothermal enhanced chemodynamic therapy of OS. The system utilizes the Fenton-like reaction activity of CuO2NPs and the photothermal conversion ability of polydopamine (PDA) to autonomously generate hydroxyl radicals in a weakly acidic tumor microenvironment and effectively kill tumor cells. In vitro experiments confirmed that it has high toxicity to osteosarcoma cells and low toxicity to normal cells. In vivo, CuO2@ZIF8@PDANPs accumulated at the bone tumor site of mice through the EPR effect. Under 808nm laser irradiation, CuO2@ZIF8@PDANPs showed significant photothermal effect, enhanced the Fenton-like reaction of CuO2 and produced -OH, thereby significantly inhibiting tumor growth. The experimental results show that CuO2@ZIF8@PDANPs combined with photothermal effect and chemodynamic therapy show good biocompatibility and anti-tumor efficacy, have potential application prospects in osteosarcoma, and provide new ideas and methods for the treatment of osteosarcoma. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0025] Figure 1 The transmission electron microscopy image (A), dynamic light scattering (DLS) (B), XPS curve (C), UV-visible spectrum (D) of the CuO2NPs prepared in Example 1, and the absorption spectrum of TMB mixed with CuO2 under different conditions to evaluate the generation of -OH (E) and the effect of temperature on the generation of -OH by CuO2 nanoparticles (F);

[0026] Figure 2 is the characterization of CuO2@ZIF8@PDANPs prepared in Example 1; wherein (A) ZIF8; (B) CuO2@ZIF8; (C) TEM image of CuO2@ZIF8@PDANPs; (D) Zeta potential of CuO2, ZIF8, CuO2@ZIF8 and CuO2@ZIF8@PDANPs; the inset in (D) shows the color of the CuO2@ZIF8@PDA suspension; (E) Fourier transform infrared spectra of ZIF8 and CuO2@ZIF8@PDANPs; (F) UV-visible absorption spectra of TMB and CuO2@ZIF8 NPs in solutions with different pH values; (G) Absorption spectra of TMB mixed with CuO2@ZIF8@PDA NPs under different conditions; (H) ESR spectra of -OH captured by DMPO in CuO2@ZIF8@PDANPs suspension; (I) is the consumption of GSH by different samples detected by DTNB method (1: pH 7.4; 2: pH 5.5; 3: pH

[0027] 5.5+ZIF8; 4: pH7.4+CuO2@ZIF8@PDANPs; 5: pH5.5+CuO2@ZIF8@PDANPs);

[0028] Figure 3 The temperature rise curve of CuO2@ZIF8@PDANPs under 808 nm near-infrared laser irradiation (A), the photothermal images of PBS and CuO2@ZIF8@PDANPS solutions at 1 minute, 4 minutes and 8 minutes, respectively (B), and the absorption spectra of TMB mixed with CuO2@ZIF8@PDANPs under different conditions (C);

[0029] Figure 4 Results of cytotoxicity tests; (A) Cytotoxicity of CuO2@ZIF8@PDANPs to HUVEC cells; (B) ZIF-8NPs; (C) CuO2@ZIF8 NPs; (D) Cytotoxicity of CuO2@ZIF8@PDA NPs to K7M2 cells; (E) Cytotoxicity of K7M2 cells irradiated by 808 nm near-infrared laser; (F) Cytotoxicity of CuO2@ZIF8@PDA+NIR to K7M2 cells;

[0030] Figure 5 The intracellular distribution of CuO2@ZIF8@PDANPs in K7M2 cells after 2 hours of co-culture, scale bar = 5 μm (A); Fluorescence images of ROS in K7M2 cells detected by DCFH-DA probe after 8 hours of co-culture with different samples, scale bar = 20 μm (B);

[0031] Figure 6 The distribution of CuO2@ZIF8@PDA NPs in tumor-bearing mice at different time points (A); the weight change curve of tumor-bearing mice after treatment with different samples (B); the optical photograph of mouse tumor tissue after 14 days of treatment (C) and the change of tumor volume (D);

[0032] Figure 7 Flow chart of the CuO2@ZIF8@PDANPs synthesized in Example 1 (A) and the anti-tumor therapy principle of CDT in vivo (B). DETAILED DESCRIPTION

[0033] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0034] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0035] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0036] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0037] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0038] The raw materials in the examples of the present invention were all obtained through commercial sources.

[0039] H2O2, CuCl2, NaOH, polyvinylpyrrolidone K30 (PVP), and 2-methylimidazole were purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0040] Ltd. 3,3′,5,5′-Tetramethylbenzidine (TMB), dopamine hydrochloride (DA), 5,5-dimethyl-1-pyrroline N -oxide (DMPO, ≥97.0%), 5,5-dithiobis(2-nitrobenzoic acid) (DTNB), and zinc nitrate hexahydrate were purchased from Aladdin Biotechnology Co., Ltd.;

[0041] BODIPY 581 / 591C11 was purchased from Thermo Fisher Scientific Inc.;

[0042] Cell counting kit-8 (CCK-8) kit, FITC, Hochest33342, lysozyme tracer red and DCFH-DA were purchased from KeyGen Biotechnology Co., Ltd.

[0043] PBS buffer, physiological saline, H&E staining solution and 4% paraformaldehyde were purchased from Yuanye Biotechnology Co., Ltd.

[0044] The preparation method of ZIF8 NPs is as follows: 73 mg Zn(NO3)2-6H2O and 82 mg 2-methylimidazole are dissolved in 1 mL of anhydrous methanol, respectively. The mixture is stirred at 650 rpm for 2 hours. The solid product is then centrifuged at 12,000 rpm, washed three times with anhydrous methanol and deionized water, and freeze-dried to obtain ZIF8 NPs.

[0045] Example 1

[0046] A method for preparing polydopamine-modified, copper peroxide-loaded ZIF8 nanoparticles, comprising the following steps:

[0047] S1. Preparation of CuO2NPs

[0048] Dissolve 500 mg of PVP in 5 mL of 0.05 M CuCl2 aqueous solution. Subsequently, 5 mL of 0.02 M NaOH was added to the solution at a flow rate of 1 mL / min under magnetic stirring at 650 rpm. Then, 0.1 mL of 10 M H2O2 was added to the solution at a flow rate of 10 μL / min to obtain a brown solution. Stirring was continued at room temperature for 30 minutes, and the PVP-coated CuO2NPs were collected by centrifugation (15,000 rpm), washed three times with deionized water and anhydrous methanol, and freeze-dried.

[0049] S2. Preparation of CuO2@ZIF8 NPs

[0050] 5 mg of CuO2NPs were dispersed in 5 mL of anhydrous methanol to obtain a CuO2NPs suspension. Then, 73 mg of Zn(NO3)2-6H2O and 82 mg of 2-methylimidazole were dissolved in 1 mL of anhydrous methanol. The two solutions were added dropwise to the above CuO2NPs suspension under stirring at 650 rpm and reacted for 2 hours. Then, the CuO2@ZIF8 NPs were centrifuged at 12,000 rpm, washed three times with anhydrous methanol and deionized water, and collected by freeze drying.

[0051] Synthesis of S3, CuO2@ZIF8@PDA NPs

[0052] 20 mg CuO2@ZIF8 NPs were dispersed in 5 mL anhydrous methanol. Subsequently, 2 mL DA solution (concentration 1.5 mg / mL, dissolved in Tris buffer solution, pH = 8.5) was added dropwise, and the mixture was reacted for 4 hours under magnetic stirring at 650 rpm to form a polydopamine film on the surface of CuO2@ZIF8NPs. Finally, the CuO2@ZIF8@PDA NPs were centrifuged at 12,000 rpm, washed three times with anhydrous methanol and deionized water, and freeze-dried to obtain CuO2@ZIF8@PDANPs.

[0053] Test example

[0054] The product prepared in Example 1 was tested and characterized by the following method:

[0055] 1. Morphological characterization

[0056] Transmission electron microscopy (TEM, JEOL TEM-100) was used to characterize the size and morphology of different samples.

[0057] The size distribution and zeta potential of the different products in Example 1 were measured by dynamic light scattering (DLS) (NanoZS90, Malvern).

[0058] The sample dry powder was mixed with KBr and the modification of CuO2@ZIF8 by PDA was analyzed by Fourier transform infrared spectrometer (FT-IR) on NEXUS-870 Fourier transform infrared spectrometer.

[0059] The UV-visible absorption curve was measured by a UV-visible-near infrared spectrophotometer (JASCO V-670). The signal of HO- was tested by electron paramagnetic resonance (EPR), and the spectrum at room temperature was recorded at a frequency of 9.85 GHz using a Bruker EMXplus-10 / 12 spectrometer (Bruker, Germany) with a variable temperature control device (Bruker ER4141 VT-I);

[0060] 2. In vitro detection of -OH

[0061] The hydroxyl radicals (-OH) generated by CuO2@ZIF8@PDA NPs were confirmed by ESR measurement using an electron paramagnetic resonance spectrometer (Bruker A300) with DMPO as a trapping agent. Briefly, 100 μL of 50 mM DMPO was added to 0.9 mL of CuO2@ZIF8@PDA NPs suspension (1 mg / mL) in a capillary at 25 °C. The capillary was then detected on an electron paramagnetic resonance spectrometer.

[0062] In order to evaluate the ability of different samples to produce -OH, the present invention uses TMB (3,3',5,5'-tetramethylbenzidine) and MB as optical probes. Prepare different sample solutions of 1 mg / mL with different pH values ​​(pH 7.4 and 5.5), and then add 100 μL of 40 μg / mL TMB solution to each solution. All solutions are incubated at different temperatures for 30 minutes, and then the ultraviolet absorption peak at a wavelength of 650 nm is measured.

[0063] The MB method was used to evaluate the ability of CuO2@ZIF8@PDA NPs to generate -OH radicals. 2 mL of CuO2@ZIF8@PDA NPs (1 mg / mL) solution with different pH values ​​(7.4 and 5.5) was mixed with 0.2 mL of methyl bromide (final concentration of 15 mmol / L) and incubated at room temperature for 2 hours. The UV-visible absorption spectrum at a wavelength of 664 nm was then measured using a UV-visible spectrophotometer, and the results of 15 mmol / L methyl bromide at pH = 5.5 were used as a comparison.

[0064] To verify the ability of PTT (photothermal therapy) to enhance -OH generation, CuO2@ZIF8@PDA NPs suspensions (1 mg / mL) with different pH values ​​were mixed with TMB (40 μg / mL). 2After 8 minutes of 808 nm near-infrared laser irradiation, the solution was incubated for another hour. Finally, the absorbance at 650 nm was measured using a UV-visible spectrophotometer.

[0065] 3. Photothermal capacity of CuO2@ZIF8@PDA NPs.

[0066] 1.2 mL CuO2@ZIF8@PDA NPs (1 mg / mL) was placed in a 1.5 mL centrifuge tube. 2 The centrifuge tube was irradiated with 808 nm near-infrared laser for 8 minutes. The temperature and thermal images were recorded by a thermal imager at different times. 1.2 mL PBS was used as a control in this experimental example.

[0067] 4. GSH consumption capacity of CuO2@ZIF8@PDA NPs

[0068] CuO2@ZIF8@PDA NPs or ZIF8 NPs (ZIF8 content was 0.1 mg / mL) were co-cultured with GSH (0.1 mmol / L) in PBS at different pH values ​​(5.5 and 7.4) for 6 hours. GSH (0.1 mmol / L) in PBS at different pH values ​​(5.5 and 7.4) was used as a control. Subsequently, DTNB (0.2 mg / mL) was added to the solution for 10 minutes respectively. The absorbance at a wavelength of 412 nm was analyzed using a microplate reader. This process was repeated three times to detect the consumption of GSH.

[0069] 5. In vitro cell experiments

[0070] Cell culture: Human umbilical vein endothelial cells (HUVEC) and mouse osteosarcoma cell line K7M2 were provided by Shanghai Institute of Cell Biology (Shanghai, China). These cells were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS) at 37°C and 5% humidity. In all experiments, the sample dose was calculated according to the amount of ZIF8.

[0071] Cytotoxicity assay: CCK-8 assay kit was used to evaluate the cytotoxicity of different samples. 4K7M2 cells were seeded onto 96-well plates at a density of 10 cells. Then, the cells were placed in a cell culture incubator under standard conditions of 37°C and 5% CO2 for a period of time until the cells reached a confluence of about 80%. After that, the culture medium was removed and the cells were rinsed twice with PBS. Then, 200 μL of culture solution containing samples of different concentrations was added to each well, and the cells were cultured for another 24 hours. Finally, 10 μL of CCK-8 solution was added to each well and cultured for another 2 hours. The absorbance of each well at a wavelength of 450 nm was measured using a microplate reader, and the cell viability of each group was calculated by comparing the absorbance value with that of the control group.

[0072] For the laser irradiation group, after adding 200 μL of culture medium containing samples of different concentrations to each well, the cells were cultured for another 2 h and then irradiated with an intensity of 1 W / cm 2 The cells were then irradiated with an 808 nm near-infrared laser for 8 min. The cells were then cultured for 24 h. Afterwards, cell viability was assessed using the CCK-8 assay kit as described above.

[0073] Cell uptake experiment: Add 1 mL of 1 mM poly-lysine solution to the confocal culture dish, and then place the dish in a cell culture incubator at 37°C and 5% CO2 for 10 minutes. Then, rinse the dish twice with PBS and inoculate K7M2 cells at 1×10 5 The cells were seeded into confocal culture dishes at a density of 100 μg / mL and cultured for 24 h. Then, the cells were rinsed twice with PBS, and 1 mL of culture medium containing FITC (fluorescent probe) modified CuO2@ZIF8@PDA NPs was added at a concentration of 25 μg / mL. After culturing for 2 h, the cells were rinsed twice with PBS, and 600 μL of Hoechst solution was added and gently mixed for 10 min. The cells were rinsed twice with PBS again, and 1 mL of PBS solution containing 1 μL of lysosomal red fluorescent probe was added and incubated for 5 min. Finally, the cells were thoroughly washed with PBS and observed using a laser scanning confocal microscope (FV3000, Olympus, Japan).

[0074] Intracellular ROS detection: K7M2 cells were cultured at 1×0 5 The number of cells was seeded into confocal culture dishes and cultured with culture medium containing ZIF-8, CuO2@ZIF8 NPs or CuO2@ZIF8@PDANPs (25 μg / mL). After 8 hours, 50 μL of DCFH-DA solution (10 μM) was added to these culture dishes and cultured for 30 minutes. Finally, the cells were rinsed with PBS and observed with a laser scanning confocal microscope (FV3000, Olympus, Japan).

[0075] 6. Establishment of osteosarcoma mouse model and in vivo anti-tumor experiments

[0076] Establishment of osteosarcoma mouse model. To establish osteosarcoma mouse model, each BALB / c female mouse (weight 19-22 g) was injected into the right axilla with 200 μL K7M2 cell suspension (concentration 1×10 7 cells / 100μL). Mice were housed in a specific pathogen-free (SPF) animal facility, with litter changed every two days and food and water replenished regularly. Tumor growth was monitored every three days. When the tumor reached an appropriate size, the mouse model was considered successfully established and subsequent experiments could be performed. All BALB / c female mice were purchased from the Center for Comparative Medicine of Yangzhou University, and all animal experiments were performed in accordance with ethical guidelines and approved by the Animal Care and Use Committee (IACUC) and the Animal Welfare Ethical Review Committee of Nanjing University (IACUC-D2103066).

[0077] In vivo biodistribution of CuO2@ZIF8@PDA NPs:

[0078] ICG (indocyanine green)-loaded CuO2@ZIF8@PDANPs were injected into tumor-bearing mice via the tail vein. The in vivo biodistribution was monitored at 1, 2, 4, 8, 12, and 24 hours after injection using the IVIS Spectrum Small Animal Imaging System (PerkinElmer, USA). After 24 hours, the mice were euthanized, and the heart, liver, spleen, lung, kidney, and tumor were dissected out for in vitro luminescence imaging using the same imaging system.

[0079] In vivo anti-tumor experiment:

[0080] The K7M2 tumor-bearing mice were randomly divided into five groups (5 mice in each group). (1) Control group: each mouse was injected with 0.1 mL PBS; (2) PBS+NIR group: each mouse was injected with 0.1 mL PBS, and then the tumor site was irradiated with 808 nm NIR laser for 8 minutes 12 hours after injection; (3) CuO2@ZIF8 group: each mouse was injected with 0.1 mL 0.4 mg / mL CuO2@ZIF8 NPs solution through the tail vein; (4)

[0081] CuO2@ZIF8@PDA group: Each mouse was injected with 0.1 mL of 0.4 mg / mL via tail vein

[0082] CuO2@ZIF8@PDA NPs solution; (5) CuO2@ZIF8@PDA+NIR group: Each mouse was injected with 0.1 mL of 0.4 mg / mL CuO2@ZIF8@PDA NPs solution via the tail vein, and then the tumor site was irradiated with 808 nm laser for 8 minutes 12 hours after injection. The mice were injected once through the tail vein every three days for a total of three treatments. The weight and tumor size of the mice were measured every two days to evaluate the anti-tumor effect of the treatment.

[0083] Histological analysis: After 14 days of treatment, mice were euthanized, and tumors, hearts, livers, spleens, lungs, and kidneys were dissected, rinsed with saline, and fixed with 4% paraformaldehyde. Organs and tumors from each group were randomly selected for pathological sections and hematoxylin and eosin (H&E) staining. Representative images of each group were taken using an optical microscope.

[0084] The characterization and detection results are as follows:

[0085] (1) Figure 1 The transmission electron microscopy image (A), dynamic light scattering (DLS), XPS curve (C) and UV-visible spectrum (D) of the CuO2NPs prepared in Example 1, and the absorption spectrum of TMB mixed with CuO2 nanoparticles under different conditions to evaluate the generation of -OH (E) and the effect of temperature on the generation of -OH by CuO2 nanoparticles (F); Figure 1 As shown, Example 1 uses PVP as a protective agent for synthesizing CuO2NPs, and uniformly shaped CuO2NPs are obtained in an alkaline solution. TEM images show that these CuO2NPs have a spherical structure with a diameter of about 5nm, showing uniform size and morphology ( Figure 1 A). Dynamic light scattering (DLS) results showed that the hydrated particle size of these CuO2NPs was approximately 16.3±4.3nm, showing a narrow particle size distribution ( Figure 1 B). XPS analysis was used to investigate the chemical state of the elements in CuO2NPs. The XPS spectrum showed two main peaks at 933.5eV and 953.5eV and two satellite peaks at 942eV and 962eV, corresponding to the Cu 2p region in CuO2NPs, indicating that Cu was in a divalent oxidation state. The binding energy peak near 532.5eV belongs to the O1s region, indicating the presence of an OO bond, while the N1s peak near 400eV represents the presence of PVP ( Figure 1 C). In the UV spectrum, CuO2NPs showed obvious characteristic absorption peaks between 300nm and 400nm, which is consistent with the literature reports ( Figure 1 D).

[0086] The CuO2NPs prepared in Example 1 will decompose into H2O2 and Cu 2+Subsequently, H2O2 2+ In the presence of TMB, CuO2NPs decompose into hydroxyl radicals (-OH). These -OH can oxidize the amino groups in TMB, thereby generating a significant absorption peak at a wavelength of 650nm. Therefore, the present invention uses TMB solution to evaluate the ability of CuO2NPs to generate hydroxyl radicals in solutions with different pH values. Figure 1 As shown in Figure E, under the condition of pH 7.4, the CuO2NPs solution did not show an obvious absorption peak at a wavelength of 650nm, which indicates that they are stable in a neutral environment and do not produce -OH. On the contrary, under weakly acidic conditions (pH 5.5), CuO2NPs produced a strong absorption peak at a wavelength of 650nm. In contrast, under weakly acidic conditions, H2O2 and TMB alone did not show an absorption peak at a wavelength of 650nm, which ultimately proved that CuO2 would decompose into Cu under acidic conditions. 2+ and H2O2, and further generates -OH through a Fenton-like reaction. These results demonstrate the pH responsiveness of CuO2 to generate -OH. According to the literature, increased temperature increases the efficiency of the Fenton reaction, thereby generating more -OH radicals. Therefore, the present invention heats the aqueous solution containing TMB and CuO2NPs to 20°C and 40°C, respectively, to study the efficiency of -OH generation at different temperatures. At 40°C, the ultraviolet absorbance value at a wavelength of 650nm was 0.658, while at 20°C it was only 0.285, indicating that more -OH ( Figure 1 F). This may be because the increase in temperature accelerates the decomposition of CuO2NPs, thereby releasing more Cu in the same time. 2+ and H2O2, and also accelerated the Fenton reaction, producing more -OH. This experimental result emphasizes that the photothermal effect improves the efficiency of the Fenton reaction in CuO2NPs, thereby increasing the generation of -OH, which is beneficial to CDT. CuO2@ZIF8 NPs are obtained by encapsulating CuO2NPs in ZIF8NPs. ZIF8 without CuO2NPs has a regular spherical structure with a particle size of about 30nm ( Figure 2 A). Since ZIF8 contains 2-methylimidazole, they have a significant positive charge (35.6 mV, Figure 2 D). The loading of CuO2NPs did not destroy the structure of ZIF-8, and CuO2@ZIF8NPs still showed a regular spherical structure. However, compared with ZIF8, the size of CuO2@ZIF8NPs increased significantly, reaching about 50nm ( Figure 2 B). In addition, due to the negatively charged CuO2NPs (-10.1mV, Figure 2D), the surface potential of CuO2@ZIF8 NPs decreased significantly from 35.6 mV of ZIF-8 to 14.3 mV ( Figure 2 D). Carefully observing the TEM image of CuO2@ZIF8 NPs, we observed black CuO2NPs with a size of about 5 nm both inside and on the surface of CuO2@ZIF8NPs ( Figure 2 B).

[0087] (2) In order to improve the biocompatibility of CuO2@ZIF8 NPs and give them photothermal properties, PDA was coated on their surface to obtain CuO2@ZIF8@PDA NPs. These NPs have a uniform spherical structure, and the particle size increases to about 70nm ( Figure 2 C). The surface of these NPs is relatively rough due to the presence of PDA. In addition, the color of the CuO2@ZIF8@PDA NPs solution changes from the white of CuO2@ZIF8 to black, which is consistent with the color of pure PDA polymer ( Figure 2 D inset). Compared with the positive surface charge of CuO2@ZIF8 NPs, CuO2@ZIF8@PDA NPs showed an obvious negative charge (-13.1 mV) ( Figure 2 D). This is because PDA contains a large number of phenolic hydroxyl groups, which carry negative charges in aqueous solution, thus bringing negative charges to CuO2@ZIF8@PDA NPs.

[0088] The chemical structure of CuO2@ZIF8@PDA NPs was studied by infrared spectroscopy. Figure 2 E). Compared with ZIF-8NPs, CuO2@ZIF8@PDA NPs have a -1 and 3110cm -1 A pair of characteristic absorption peaks appeared at 3409cm, which are caused by the stretching vibration of the primary amine in dopamine. -1 The broad peak at 1579 cm -1 The absorption peak at 1100 cm -1 Up to 1350cm -1 The peaks in the range correspond to the stretching vibrations of CO and CN bonds, which are mainly attributed to the phenolic oxygen and amino nitrogen in PDA.

[0089] The remaining absorption peaks of CuO2@ZIF8@PDA NPs are consistent with those of pure ZIF-8, indicating that the PDA coating did not destroy the functional groups or structure of ZIF-8 NPs. These data confirm the successful preparation of CuO2@ZIF8@PDA NPs, and the CuO2 content determined by ICP is 6.3wt%. The stability of different NPs in PBS solution at 4°C and pH 7.4 was studied. All samples remained stable in PBS solution for 10 days. .

[0090] We expected that CuO2NPs encapsulated in CuO2@ZIF8@PDA NPs could maintain their ability to generate hydroxyl radicals, thereby exerting a chemokinetic effect in treating tumors. Therefore, the ability of different NPs to generate hydroxyl radicals was evaluated using the TMB method. Figure 2 F shows the UV-visible absorption spectra of TMB in CuO2@ZIF8 NP dispersions at different pH values. In the absence of CuO2@ZIF8 NPs, CuO2 does not decompose to produce -OH, and no characteristic oxidized TMB absorption peak is observed at 650 nm at pH 5.5. However, when CuO2@ZIF8 NPs are present in this acidic solution, a clear oxidized TMB absorption peak appears at a wavelength of 650 nm. In contrast, at pH 7.4, no oxidized TMB absorption peak is detected at a wavelength of 650 nm even when CuO2@ZIF8 NPs are present in the solution. These data indicate that CuO2 encapsulated in CuO2@ZIF8 NPs can maintain its ability to respond to pH and generate -OH.

[0091] Methylene blue (MB) was used as an indicator to evaluate the ability of CuO2@ZIF8@PDANPs to generate -OH. Methylene blue is a redox indicator that is blue in normal conditions and has a maximum absorption peak at 664nm. Due to the presence of its intermediate sulfur atom, MB can react with -OH to generate hydroxymethylene blue, resulting in the disappearance of the 664nm absorption peak and a color change from blue to colorless. We determined whether -OH was present in the system by measuring the absorbance change of methyl bromide at 664nm. Figure 2As shown in Figure G, under pH 5.5, CuO2@ZIF8@PDA NPs can significantly reduce the absorbance of MB at 664nm wavelength from 0.993 in the control group to 0.273, indicating that the PDA coating did not affect the properties of CuO2NPs, and they can still produce -OH to oxidize MB under acidic conditions. However, we also observed that CuO2@ZIF8@PDA NPs can reduce the absorbance of MB even under neutral conditions. This may be due to the abundant phenolic hydroxyl groups in PDA, which interfered with the experimental results. Further analysis showed that the same amount of CuO2@ZIF8@PDA NPs only reduced the absorbance at 664nm wavelength by 0.521 in neutral solution, while it decreased by 0.72 under weakly acidic conditions. This confirms that CuO2@ZIF8@PDA NPs will produce -OH under acidic conditions, thereby enhancing the oxidation capacity of the system. In order to verify that the ROS generated by CuO2@ZIF8@PDA NPs are indeed -OH, DMPO was used as a spin trap to detect the EPR spectrum of ROS generated by CuO2@ZIF8@PDA NPs at pH 5.5 ( Figure 2 H). CuO2@ZIF8@PDA NPs showed a characteristic -OH 1:2:2:1 peak shape. Therefore, CuO2@ZIF8@PDA NPs generated -OH through a Fenton-like reaction, thus exerting a CDT effect in tumor therapy.

[0092] GSH highly expressed in tumor sites will consume -OH produced by Fenton reaction, thus inhibiting the therapeutic effect of CDT. Removing GSH from tumor sites can enhance the therapeutic effect of CDT. We studied the ability of CuO2@ZIF8@PDA NPs to react with GSH. In a weakly acidic system, CuO2@ZIF8@PDA NPs undergo a Fenton-like reaction to generate Cu 2+ and -OH. Cu 2+ Can react with GSH overexpressed in tumor cells (GSH+Cu 2+ =GSSG+Cu + ), which can not only reduce the content of GSH in tumor tissue, but also generate Cu with stronger ability to catalyze Fenton reaction. + , thereby enhancing the CDT effect. We used the DTNB method to detect the ability of different samples to consume GSH ( Figure 2 I). Acidic or neutral media do not consume GSH. Under acidic conditions, the GSH content in the ZIF8 system (pH5.5+ZIF8) decreased slightly, which may be due to the degradation of ZIF8 to generate Zn under weakly acidic conditions. 2+ Ion, Zn 2+ions bind to GSH to form a complex, resulting in a reduction in GSH. CuO2@ZIF8@PDA NPs also consume a small amount of GSH under neutral conditions. Although CuO2 and ZIF8 remain stable under neutral conditions and do not release H2O2 and Zn 2+ However, PDA interacts with GSH and consumes some GSH. Under weakly acidic conditions, CuO2@ZIF8@PDA NPs consumed more than 50% of GSH within 6 hours. All these results indicate that CuO2@ZIF8@PDA NPs can be degraded to produce Cu under acidic conditions. 2+ , undergoing a Fenton-like reaction with H2O2, consuming intracellular GSH, thereby producing a CDT effect on tumor cells.

[0093] (3) PDA not only has good biocompatibility, but also has significant photothermal conversion ability, which can enhance the CDT effect of CuO2@ZIF8@PDA NPs. Therefore, the present invention conducted a photothermal conversion experiment to evaluate the photothermal ability of PDA. Under 808nm near-infrared laser irradiation, the temperature of the PBS control solution remained almost unchanged, indicating that laser irradiation alone does not cause significant changes in the solution temperature ( Figure 3 A and 3B). In contrast, the temperature of the CuO2@ZIF8@PDA NPs solution increased significantly, reaching 35.1°C within 4 minutes and 41°C within 8 minutes after laser irradiation. According to literature reports, tumor tissues have poorer tolerance to high temperatures than normal tissues. Within a specific temperature range (such as 40°C-43°C), tumor cells undergo apoptosis and necrosis, while normal cells are not affected. Therefore, we chose 40°C as the temperature for photothermal therapy in in vitro and in vivo experiments. In the above experiments, CuO2NPs have a stronger ability to generate -OH at 40°C compared with room temperature. Therefore, we irradiated the CuO2@ZIF8@PDA NPs solution with 808nm laser and used the photothermal effect of PDA to increase the temperature of the system. We used TMB as a probe to detect -OH and evaluated the ability of CuO2@ZIF8@PDA NPs to generate -OH at different temperatures. Acidic PBS (pH 5.5) solution without laser irradiation did not show obvious UV absorption peaks ( Figure 3 C), while the acidic PBS solution after 808 nm laser irradiation showed only a weak UV absorption peak, which may be due to the partial oxidation of TMB by near-infrared light. The CuO2@ZIF8@PDA NPs solution under neutral conditions also did not show an obvious TMB oxidation absorption peak, indicating that no -OH was generated under neutral conditions. This result is consistent with our previous Figure 2G. In contrast, CuO2@ZIF8@PDA NPs under acidic conditions showed a clear UV absorption peak, indicating that -OH was generated and TMB was oxidized. When the acidic CuO2@ZIF8@PDANPs solution was irradiated for 8 minutes, the system temperature rose to 40°C, and the UV absorption peak at 650nm increased from 0.126 to 0.186, indicating that high temperature increased the efficiency of CuO2@ZIF8@PDA NPs in generating -OH. This finding is consistent with previous research results that CuO2NPs will produce more -OH at high temperatures. The above studies show that under near-infrared laser irradiation, CuO2@ZIF8@PDA NPs have the ability to enhance tumor chemodynamic therapy through photothermal effect.

[0094] (4) To evaluate the efficacy of CuO2@ZIF8@PDA NPs in treating OS, we studied the toxicity of different samples on K7M2 mouse bone tumor cells. Figure 4 A shows the viability of HUVEC cells after treatment with CuO2@ZIF8@PDA NPs for 24 hours. We found that even at a concentration of 50 μg / mL (based on the content of ZIF8), CuO2@ZIF8@PDA NPs did not show significant cytotoxicity to HUVEC cells, and the cell viability remained above 80%. This indicates that the cytotoxicity of CuO2@ZIF8@PDANPs to normal cells is negligible ( Figure 4 A). Pure ZIF-8NPs had no obvious cytotoxicity to K7M2 cells. At a concentration of 50 μg / mL, the survival rate of K7M2 cells was still higher than 80% ( Figure 4 B). In contrast, CuO2@ZIF8 NPs showed significant toxicity to K7M2 cells, with a lethality of approximately 50% at a concentration of 25 μg / mL ( Figure 4 C) We speculate that in the slightly acidic microenvironment of K7M2 cells, ZIF8 will degrade, releasing CuO2NPs and further producing H2O2. 2+ / Cu + In the presence of , a Fenton-like reaction occurs, producing -OH that kills tumor cells. Figure 4 C and Figure 4 D, we found that the cytotoxicity of the CuO2@ZIF8 group was slightly higher than that of the CuO2@ZIF8@PDA group ( Figure 4D). This is because PDA has good biocompatibility, which reduces the toxicity of CuO2@ZIF8@PDA NPs. Previous studies have confirmed that the photothermal effect can promote CuO2@ZIF8@PDA NPs to produce more -OH, thereby enhancing its ability to kill tumor cells. Therefore, the present invention studies the effect of near-infrared laser irradiation on the viability of K7M2 cells. Simple near-infrared laser irradiation did not significantly affect the survival rate of K7M2 cells ( Figure 4 E). However, CuO2@ZIF8@PDANPs showed strong cytotoxicity under near-infrared laser irradiation. When the concentration was 25 μg / mL, the survival rate of K7M2 cells was only about 24%, which was significantly lower than that of CuO2@ZIF8 NPs and CuO2@ZIF8@PDA NPs without laser irradiation ( Figure 4 F). When the concentration was 50 μg / mL, the survival rate of K7M2 cells dropped to about 10%, indicating that CuO2@ZIF8@PDA NPs had significant cytotoxicity under laser irradiation. This is because under 808 nm near-infrared laser irradiation, CuO2@ZIF8@PDA NPs produced a synergistic treatment effect of PTT and CDT. At the same time, the temperature increase caused by PTT further enhanced the Fenton-like reaction of CuO2@ZIF8@PDA and promoted the generation of -OH, showing a more effective therapeutic effect than CDT treatment alone. In summary, CuO2@ZIF8@PDA NPs can achieve the synergistic effect of PTT and CDT through photothermally enhanced Fenton-like reactions, thereby improving its anti-tumor ability.

[0095] (5) The cytotoxicity of NPs is directly related to their cellular uptake efficiency and intracellular distribution. Therefore, we labeled CuO2@ZIF8@PDANPs with fluorescein isothiocyanate (FITC) to study the uptake behavior of CuO2@ZIF8@PDA NPs by K7M2 cells. Figure 5 As shown in A, the cell nucleus was stained blue by Hoechst dye, and the lysosome was marked red by Lyso-Tracker Red. After the green CuO2@ZIF8@PDA NPs were incubated with cells for 2 hours, the green fluorescence emitted by the CuO2@ZIF8@PDA NPs overlapped with the red fluorescence of the lysosomes (appearing yellow) and accumulated near the nucleus, indicating that K7M2 cells effectively absorbed the CuO2@ZIF8@PDA NPs through the endosomal / lysosomal pathway. Upon closer inspection, some green fluorescence was inconsistent with the red fluorescence, indicating that a small amount of CuO2@ZIF8@PDA NPs may be decomposed in acidic lysosomes and then enter the cytoplasm.

[0096] CuO2@ZIF8@PDA NPs can generate reactive oxygen species (ROS) in tumor cells. The DCFH-DA probe was used to detect the ROS levels in K7M2 cells treated with different samples ( Figure 5 B). It is noteworthy that cells in the control group (PBS) and ZIF-8 group showed weak green fluorescence, indicating low ROS levels. This is due to the reaction of endogenous ROS in tumor cells with the DCFH-DA probe to produce green signals. In contrast, both the CuO2@ZIF8@PDA group and the CuO2@ZIF8 group cultured with K7M2 cells showed strong fluorescence, indicating a high concentration of ROS in the cells. We believe that these NPs carry a large amount of CuO2NPs, which decompose in the weakly acidic environment of tumor cell lysosomes, releasing Cu 2+ and H2O2, subsequently generating a large amount of -OH. As a result, the cells exhibited a strong green fluorescence.

[0097] The cytotoxicity of NPs is directly related to their cellular uptake ability and distribution within cells. Therefore, we labeled CuO2@ZIF8@PDA NPs with fluorescein isothiocyanate (FITC) to study the uptake behavior of CuO2@ZIF8@PDA NPs by K7M2 cells. Figure 5 As shown in A, the cell nucleus was stained blue by Hoechst dye, and the lysosome was marked red by Lyso-Tracker Red. After the green CuO2@ZIF8@PDA NPs were incubated with cells for 2 hours, the green fluorescence emitted by CuO2@ZIF8@PDA overlapped with the red fluorescence of the lysosomes (appearing yellow) and accumulated near the nucleus, indicating that K7M2 cells effectively absorbed CuO2@ZIF8@PDA NPs through the endosomal / lysosomal pathway. Upon closer inspection, some green fluorescence was inconsistent with red fluorescence, indicating that a small amount of CuO2@ZIF8@PDA NPs may be decomposed in acidic lysosomes and then enter the cytoplasm.

[0098] (6) Nanomedicines can passively target tumor tissues through the enhanced permeability and retention (EPR) effect, thereby improving drug utilization efficiency. Therefore, we used fluorescence technology to study the distribution of CuO2@ZIF8@PDA NPs in osteosarcoma model mice. Figure 6As shown in A, the blue area of ​​the right upper limb of the mouse indicates the location of the tumor. After tail vein injection of CuO2@ZIF8@PDA NPs, obvious accumulation was observed mainly in the abdominal cavity within 1-2 hours. After 4 hours, obvious blue signals appeared in the tumor tissue. From 8 to 12 hours, CuO2@ZIF8@PDA NPs continued to accumulate in the tumor tissue, and the fluorescence intensity was strongest at 12 hours. After extending the observation time to 24 hours, the fluorescence intensity in the tumor tissue decreased due to the metabolism and decomposition of CuO2@ZIF8@PDA NPs in the body ( Figure 6 A) Subsequently, the mice were euthanized, and their major organs and tumors were harvested for fluorescence intensity analysis.

[0099] The present invention established a mouse subcutaneous osteosarcoma model to evaluate the in vivo anti-tumor efficacy of these samples. The mice were randomly divided into five groups and injected with PBS, PBS-NIR, CuO2@ZIF8, CuO2@ZIF8@PDA NPs, and CuO2@ZIF8@PDA NPs-NIR, respectively, with a dose of 2 mg / kg (in terms of ZIF8) in each group. In the photothermal therapy experiment, the tumor site was irradiated with an 808nm near-infrared laser 12 hours after injection. Body weight and tumor volume were recorded every two days. After 14 days of treatment, all mice survived. Figure 6 As shown in B, during the treatment period, there was no significant change in the body weight of mice in each group, which indicated that all samples had good biocompatibility. Figure 6 C and 6D show the images of the resected tumors on day 14 and the changes in relative tumor volume. Irradiation with PBS and 808 nm NIR laser alone had no effect on tumor growth. In contrast, the tumors in the CuO2@ZIF8 NPs group and the CuO2@ZIF8@PDANPs group were significantly smaller than those in the PBS group and the PBS-NIR group, and the tumor volume increased by about 4 times relative to each other. This confirms that CuO2@ZIF8 and CuO2@ZIF8@PDA have CDT effects and can inhibit tumor growth. It is worth noting that the tumor volume was the smallest after mice were injected with CuO2@ZIF8@PDA NPs and received laser irradiation at the tumor site, and the relative increase in tumor volume was less than 2 times compared with the control group, showing the best tumor growth inhibition effect. This is mainly due to the synergistic effect of PTT and CDT, which not only directly kill tumor cells by increasing temperature, but also produce more hydroxyl radicals -OH through heat-enhanced Fenton-type reactions, thereby more effectively eliminating tumor cells.

[0100] In summary, the present invention successfully designed and prepared CuO2@ZIF8@PDA NPs for photothermal enhanced chemodynamic therapy of OS. The system utilizes the Fenton-like reaction activity of CuO2NPs and the photothermal conversion ability of polydopamine (PDA) to autonomously generate hydroxyl radicals in a weakly acidic tumor microenvironment and effectively kill tumor cells. In vitro experiments confirmed that it has high toxicity to osteosarcoma cells and low toxicity to normal cells. In vivo, CuO2@ZIF8@PDA NPs accumulated at the bone tumor site of mice through the EPR effect. Under 808nm laser irradiation, CuO2@ZIF8@PDANPs showed significant photothermal effect, enhanced the Fenton-like reaction of CuO2 and produced -OH, thereby significantly inhibiting tumor growth. The experimental results show that CuO2@ZIF8@PDANPs combined with photothermal effect and chemodynamic therapy show good biocompatibility and anti-tumor efficacy, have potential application prospects in osteosarcoma, and provide new insights and methods for the treatment of osteosarcoma.

[0101] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A polydopamine-modified, copper peroxide-loaded ZIF8 nanoparticle, characterized in that: The method uses zeolite imidazoline framework-8 as a matrix, and CuO2NPs are uniformly modified in the zeolite imidazoline framework-8 to form CuO2@ZIF8 NPs. The polydopamine membrane is coated on the surface of the CuO2@ZIF8 NPs in the form of a membrane.

2. A method for preparing the polydopamine-modified, copper peroxide-loaded ZIF8 nanoparticles according to claim 1, characterized in that: Using methanol solution of Zn(NO3)2 and 2-methylimidazole as raw materials, CuO2NPs were added in the process of preparing zeolite imidazoline framework-8 to obtain CuO2NP-modified zeolite imidazoline framework-8, namely CuO2@ZIF8 NPs; then a polydopamine film was formed by in situ polymerization on the surface of CuO2@ZIF8 NPs to obtain polydopamine-modified, copper peroxide-loaded ZIF8 nanoparticles.

3. The method according to claim 2, characterized in that The steps include: Polyvinyl pyrrolidone was added to the aqueous solution of copper salt, and then alkali solution and hydrogen peroxide were added in sequence under stirring. After the reaction was complete, the CuO2NPs coated with PVP were obtained by centrifugation. The methanol solution of Zn(NO3)2 and the methanol solution of 2-methylimidazole were respectively added dropwise to the methanol suspension of CuO2NPs for reaction, and the CuO2@ZIF8 NPs were obtained by centrifugation. The CuO2@ZIF8 NPs are dispersed in anhydrous methanol, and a dopamine solution is added dropwise under stirring to form a polydopamine film on the surface of the CuO2@ZIF8 NPs, thereby obtaining polydopamine-modified, copper peroxide-loaded ZIF8 nanoparticles.

4. The method according to claim 3, characterized in that: The copper salt is copper chloride, copper nitrate or copper sulfate; and / or the alkali solution is sodium hydroxide solution or potassium hydroxide solution.

5. The method according to claim 3, characterized in that: The mass ratio of the CuO2@ZIF8 NPs to dopamine is 1:(0.1-1); the dopamine solution is dopamine dissolved in a Tris buffer solution, pH=8.5, and the concentration is 1.5 mg / mL.

6. The method according to claim 3, characterized in that The mass ratio of the CuO2NPs, Zn(NO3)2 and 2-methylimidazole is 5:73:

82.

7. The method according to claim 3, characterized in that The added amount ratio of the aqueous solution of the copper salt to polyvinyl pyrrolidone is 0.05 mol: 500 mg; and / or the molar ratio of the aqueous solution of the copper salt to the hydrogen peroxide is 0.05: 1; the flow rate when the hydrogen peroxide is added dropwise is 10 μL / min.

8. The method according to claim 3, characterized in that The reaction time for preparing the CuO2NPs is 30min; and / or the reaction time for preparing the CuO2@ZIF8NPs is 2h; and / or the reaction time for forming a polydopamine film on the surface of the CuO2@ZIF8NPs is 4h.

9. Use of the polydopamine-modified, copper peroxide-loaded ZIF8 nanoparticles according to claim 1 in the preparation of anti-osteosarcoma drugs.

10. The use according to claim 9, characterized in that The anti-osteosarcoma drug is a drug for treating osteosarcoma with photothermal enhanced chemodynamic therapy.

Citation Information

Patent Citations

  • Photo-thermal anti-osteosarcoma and selective osteosarcoma killing particles, preparation method and application

    CN114452387A

  • CuO-ZIF-8 composite nanomaterial capable of sterilizing by utilizing visible light as well as preparation method and application of CuO-ZIF-8 composite nanomaterial

    CN114766514A

  • BSA-ZIF-8 / CuO2 nano composite material as well as preparation and application of BSA-ZIF-8 / CuO2 nano composite material

    CN117752820A

  • CuO (at) ZIF-8 (at) PDA-Ab2 enzyme-labeled antibody and application thereof

    CN118641746A

Cited By

  • Copper-cobalt bimetallic nanoreactor for generating active nitrogen as well as preparation method and application of copper-cobalt bimetallic nanoreactor

    CN121082327A

  • A copper-cobalt bimetallic nanoreactor for generating active nitrogen and a preparation method and application thereof

    CN121082327B